Translating the world : toward a new history of German literature around 1800 - Tautz, Birgit (Max Kade German-American Research Institute series., 2018)
"A narrative of German literary history in the late eighteenth and early nineteenth centuries. Examines the intersection of literary and national imagination through the lens of Germany's emerging global networks and how they were rendered in two very different German cities: Hamburg and Weimar"--Provided by publisher